Different Methods & Approaches of AI Ethics: Navigating AI Ethics to Practice - Bleher, Hannah; Hille, Eva Maria (Summer School "Artificial Intelligence, Ethics & Human Rights", 2022)
In the field of AI ethics, there are different approaches to how ethical theory can be put into practice. Each conceptual approach focuses differently on how to avoid a theory-practice gap and instead interweave both theory and practice. These different foci, such as a design-, principles- or stakeholder-orientation, however, have benefits and shortcomings. In this contribution, we provide an overview of current approaches of applied AI ethics and their opportunities and pitfalls. In addition to a systematization of conceptual approaches, specific aspects and methodological approaches are put up for discussion in order to interweave theory and practice of AI ethic